The role of law in the study of the relation genes with violence and behavior, and their consequences - Hadi Salih, Salah (International Journal of Psychosocial Rehabilitation, 2020)
Progress and development in behavioral genetics research and the relationship of genes to violence have reached the point where genes are carefully identified and identified to make people with these genes more predisposed to crime, aggression, and violence. An important question that now arises in criminal justice is the extent to which the results of these studies are being used to investigate the facts and to ensure rights by using these new criminal evidences. So far, there have been many studies on the relationship of genetic material in humans with the onset of violence and aggression or the emergence of certain behaviors that require serious attention. In this study, the role of chromosomes and genes in the development of violence and aggression in humans was discussed, and on the other hand, legal and judicial issues related to these cases were discussed with a number of trials in the countries of the world that used the role of genes and chromosomes as defense evidence for mitigation or exempting the defendants from responsibility for the crime. There seems to be a great tendency among the international judiciary to go deeper into the role of genetic material in violence, crime, and behavior to the extent that they tend to use accurate scientific evidence when making a judgment. This study concludes that the findings of behavioral genetics research call upon all judicial institutions and officials to pay high attention to these results and to study the possibility of using them even on a small scale as evidence in the courts for the purpose of developing the capacity of the Iraqi judiciary to guarantee the rights of the individual.